Suspected brain metastasis from lung cancer mimicking intracerebral hemorrhage: A case report. Issue 10 (March 2018) - Ma, Rui; Fang, Shao-Kuan; Hou, Shuai; Wang, Xue; Meng, Hong-Mei
Abstract: Rationale: Hemorrhage rarely occurs in a solitary brain metastasis from lung carcinoma. Patient concerns: We report on a 54-year-old man who presented with a severe headache for 4 days. Diagnoses: Based on computed tomography and magnetic resonance imaging enhancement, the patient was diagnosed with a suspected hemorrhagic brain metastasis from lung carcinoma. Interventions: The patient's family rejected a pathological examination. Outcomes: The patient's family requested discharge after diagnosis. Lessons: The present case emphasizes the need to consider hemorrhagic metastasis as a differential diagnosis in patients presenting with solitary intracerebral hemorrhage whose location is uncommon, especially when the poor general state of the patient cannot be attributed to hypertensive intracerebral hemorrhage.